PENGUATAN LITERASI AKADEMIK GURU MELALUI PELATIHAN PENULISAN KARYA ILMIAH - Darnawati; Jamiludin; Asna Wirayanti; Isna (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2024)
Scientific writing is an essential tool for teachers to enhance professionalism, support the development of knowledge, and improve the quality of education. However, not all teachers possess adequate skills and confidence in writing scientific papers, from ideation to publication. This community service program aims to provide intensive training on effective strategies for writing scientific papers tailored for teachers. The training encompasses several stages, including identifying and developing ideas, systematic writing in accordance with scientific standards, mastering referencing and citation techniques, and strategies for selecting and submitting manuscripts to academic journals. The methods used include lectures, group discussions, simulations, and direct mentoring. This program is expected to improve teachers' skills in producing high-quality scientific papers and encourage their active participation in academic publishing. The outcomes of this activity demonstrate a significant improvement in teachers' understanding and ability to write scientific papers, as well as their enthusiasm for continuing independent writing activities. Thus, this program contributes to strengthening teachers' professional capacities and enhancing the overall quality of education.